Cropping systems for Vertisols in the Ethiopian highlands - Berhe, Kahsay; Tedla, A.; Mohamed-Saleem, M.A. (Ethiopian Agricultural Research Organization, 2001)
This paper ilustrates the principle determining cropping systems for Vertisols by reviewing work in the highlands of Ethiopia. The types of cropping systems that can be applicable in the different Vertisol environments are briefly described. These cropping systems include single cropping; multiple cropping; sequential cropping; intercropping; relay cropping; home gardens; alley cropping; and ratoon cropping. Soil fertility in relation to nitrogen, phosphorus, and potassium is also discussed. The paper also looks into rainfall differences in Vertisol areas. Other topics of discussion include weeds; crop pests; and water logging.